Generation of focal mutations and large genomic deletions in the pancreas using inducible in vivo genome editing. (6th June 2019) - Mishra, Amrendra; Emamgholi, Fatemeh; Erlangga, Zulrahman; Hartleben, Björn; Unger, Kristian; Wolff, Katharina; Teichmann, Ulrike; Kessel, Michael; Woller, Norman; Kühnel, Florian; Dow, Lukas E; Manns, Michael P; et al.
Abstract: Beyond the nearly uniform presence of KRAS mutations, pancreatic cancer is increasingly recognized as a heterogeneous disease. Preclinical in vivo model systems exist, but with the advent of precision oncology, murine models with enhanced genetic flexibility are needed to functionally annotate genetic alterations found in the human malignancy. Here, we describe the generation of focal gene disruptions and large chromosomal deletions via inducible and pancreas-specific expression of Cas9 in adult mice. Experimental mice are derived on demand directly from genetically engineered embryonic stem cells, without the need for further intercrossing. To provide initial validation of our approach, we show that disruption of the E3 ubiquitin ligase Rnf43 accelerates Kras G12D -dependent tumourigenesis. Moreover, we demonstrate that this system can be used to rapidly interrogate the impact of complex cancer-associated alleles through the generation of a previously unstudied 1.2 megabase deletion surrounding the CDKN2A and CDKN2B tumour suppressors. Thus, our approach is capable of reproducibly generating biallelic and precise loss of large chromosomal fragments that, in conjunction with mutant Kras, leads to development of pancreatic ductal adenocarcinoma with full penetrance. Abstract : The integration of pancreas-directed inducible CRISPR/Cas9 technology into embryonic stem-cell-based genetically engineered mouse models is a highly versatile tool to interrupt the function of individual genes, as well as to create large homozygous organ-specific deletions in multiallelic mice.